Analisis Promosi Offline yang Dimediasi Insentif Aktivitas Marketing Terhadap Keputusan Pembelian Analysis of Offline Promotion Mediated by Marketing Activity Incentives on Purchasing Decisions - Anggriany, Novita Sari; Triana, Dewi; Linawati, Linawati (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
This study aims to analyze the effect of offline promotion mediated by marketing activity incentives on purchasing decisions at Honda Car Dealer PT. Sumber Baru Global. This type of research is descriptive quantitative research. The population in this study consists of consumers who saw the product promotion offline and observed marketing activities both through exhibitions and by directly visiting the Dealer. The sampling technique used is purposive sampling, totaling 90 respondents. The instrument used is a questionnaire. The data analysis technique used is path analysis.The results of the study show that (1) Offline promotion has a significant effect on purchasing decisions at Honda Car Dealer PT. Sumber Baru Global Cilacap, with p < 0.05. (2) Offline promotion has a significant effect on marketing activity incentives at Honda Car Dealer PT. Sumber Baru Global Cilacap, with p < 0.05. (3) Marketing activity incentives have a significant effect on purchasing decisions at Honda Car Dealer PT. Sumber Baru Global Cilacap, with p < 0.05. (4) Offline promotion has a significant effect on purchasing decisions at Honda Car Dealer PT. Sumber Baru Global Cilacap mediated by marketing activity incentives,with, p < 0,05.